2021
DOI: 10.3390/cancers13235873
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Matrix Environment of Clear Cell Renal Cell Carcinoma Determines Cancer Associated Fibroblast Growth

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common kidney cancer and is often caused by mutations in the oxygen-sensing machinery of kidney epithelial cells. Due to its pseudo-hypoxic state, ccRCC recruits extensive vasculature and other stromal components. Conventional cell culture methods provide poor representation of stromal cell types in primary cultures of ccRCC, and we hypothesized that mimicking the extracellular environment of the tumor would promote growth of both tumor and stromal cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…This appears to be due, in large part, to the activation of pathways that regulate tumor cell viability and aggressive behavior. Indeed, stromal nicotinamide N-methyltransferase (NNMT) is necessary and sufficient for CAF function (i.e., expression of CAF biomarkers, cytokine secretion, deposition of an oncogenic ECM [ 113 ]) in high-grade serous carcinoma [ 114 ]. Elevated NNMT expression defined, in part, the metastatic stromal proteome and supports ovarian cancer proliferation, migration and distal spread.…”
Section: Cafs Confer Resistance To Chemotherapymentioning
confidence: 99%
“…This appears to be due, in large part, to the activation of pathways that regulate tumor cell viability and aggressive behavior. Indeed, stromal nicotinamide N-methyltransferase (NNMT) is necessary and sufficient for CAF function (i.e., expression of CAF biomarkers, cytokine secretion, deposition of an oncogenic ECM [ 113 ]) in high-grade serous carcinoma [ 114 ]. Elevated NNMT expression defined, in part, the metastatic stromal proteome and supports ovarian cancer proliferation, migration and distal spread.…”
Section: Cafs Confer Resistance To Chemotherapymentioning
confidence: 99%
“…The proteomics are employed to identify the ECM compositions of urologic cancers. Clear cell renal cell carcinoma (ccRCC) is found that the collagen type VI, fibronectin, and tenascin C are significantly upregulated compared with healthy kidney cortex [ 165 ]. CRPC has upregulation of collagen type I, fibronectin, vitronectin, and laminin compared with normal prostate tissues [ 166 ].…”
Section: Bioprinting To Mimic the Urological Tmementioning
confidence: 99%
“…Three-dimensional fibrin cultures of 786-O, 786-O FOXD1null , and primary RCC cell lines were created following our previously reported protocol [ 9 ]. In summary, 3D cultures were generated by combining fibrinogen (MilliporeSigma, Burlington, MA, USA cat#F8630) at a 1:1 ratio with cells suspended in a culture media, with or without the addition of ECM proteins.…”
Section: Methodsmentioning
confidence: 99%
“…All tissue specimens and associated medical information received were de-identified using an honest broker system. Samples were processed as previously described [ 9 ]. Fresh tumor tissue samples were diced and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation